Entre trajetórias e relações familiares: modos de vida, narrativas e experiências de trabalhadores em Guaíra, Paraná (1960-2019) - Silva, Vanderson Wiliam Ribeiro (2024)
The text aimed to analyze the experiences, trajectories, and family relationships of agricultural workers engaged in productive activities in Guaíra (Western Paraná) starting in the 1960s. In this context, the dissertation reflected on the ways of life constructed by individuals based on their social trajectories and the construction of memories and narratives around working and shaping their identities as workers. To this end, I used interviews collected during fieldwork as the primary source, also observing how the interviewees interpreted their arrival process in Guaíra and how they established living spaces, whether in the city or primarily in rural areas. Through this discussion, the following aspects can be reflected upon i) social trajectories shaped by the pursuit of work and better living conditions; ii) family relationships and work from childhood, as well as its moral implications in the present; iii) the experiences of exploitation in rural areas based on the work relationships encountered by the interviewees.